The Role of Work Stress in Mediating the Influence of Emotional Intelligence and Spiritual Intelligence on Nurse Performance at Bunda Hospital Kandangan Surabaya - Niken Revalasha; Muhadjir Anwar; Hesty Prima Rini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The significance of having human resources within the company is one of the most important elements in order for a business or company to run well: The aim of this research is to identify the effects of: (1) Emotional Intelligence, (2) Spiritual Intelligence, (3) Stress related to emotional intelligence, (4) Stress related to spiritual intelligence, to the nurse performance. The samples taken for the research are the entire nurses in "Bunda Hospital" - Kandangan Surabaya. The research requires samples the total of 76 nurses. Data collection was carried out using the instrument of questionnaire shared to the respondent. Partial Least Square using the method of Smart PLS software was used for data analysis technique. The result of the research has shown followings: (1) Emotional Intelligence haven’t given positive contribution to the nurse performance, (2) Spiritual Intelligence have given positive contribution to the nurse performance, (3) Working stress has contributed to the impact of emotional intelligence, (4) Working stress has contributed to the impact of spiritual intelligence.